In-situ forming injectable GFOGER-conjugated BMSCs-laden hydrogels for osteochondral regeneration - Mi Yeon Ha; Dae Hyeok Yang; Su Jung You; Hyun Joo Kim; Heung Jae Chun (npj Regenerative Medicine, 2023)
Abstract The collagen-mimetic peptide GFOGER possesses the chondrogenic potential and has been used as a cell adhesion peptide or chondrogenic inducer. Here, we prepared an injectable in situ forming composite hydrogel system comprising methoxy polyethylene glycol-b-polycaprolactone (MPEG-PCL) and GFOGER-conjugated PEG-PCL (GFOGER-PEG-PCL) with various GFOGER concentrations based on our recently patented technology. The conjugation of GFOGER to PEG-PCL was confirmed by 1H NMR, and the particle size distribution and rheological properties for the sol-gel transition behavior of the samples with respect to the GFOGER content were evaluated systemically. In vitro experiments using rat bone marrow-derived mesenchymal stem cells (BMSCs) revealed that the GFOGER-PEG-PCL hydrogel significantly enhanced expression of integrins (β1, α2, and α11), increased expression of FAK, and induced downstream signaling of ERK and p38. Overexpression of chondrogenic markers suggested that BMSCs have the potential to differentiate into chondrogenic lineages within GFOGER-PEG-PCL samples. In vivo studies using a rat osteochondral defect model revealed that transplanted BMSCs with GFOGER0.8-PEG-PCL survived at the defect with strong chondrogenic expression after 4 weeks. The stem cell-laden GFOGER0.8-PEG-PCL hydrogel produced remarkable osteochondral regeneration at 8 weeks of transplantation, as determined by histological findings and micro-CT analysis. The histomorphological score in the GFOGER0.8-PEG-PCL + BMSCs group was ~1.7-, 2.6-, and 5.3-fold higher than that in the GFOGER0.8-PEG-PCL, MPEG-PCL, and defect groups, respectively. Taken together, these results provide an important platform for further advanced GFOGER-based stem cell research for osteochondral repair.